A concise guide to nuclear medicine - Elgazzar, Abdelhamid H. 1949- (Springer, 2011)
Nuclear medicine is an important component of modern medicine that should be familiar to all medical students and professionals in various health care disciplines. This easy-to-use book is designed to acquaint readers with the basic principles of nuclear medicine, the instrumentation used, the gamut of procedures available, and the basis for selecting specific diagnostic or therapeutic procedures and interpreting results. After an introductory chapter on the history, technical basis, and scope of nuclear medicine, a series of chapters are devoted to the application of nuclear medicine techniques in the different body systems. In addition, the use of nuclear medicine methods within oncology is carefully examined, covering diagnosis, staging, assessment of treatment response, radiotherapy planning, and the sentinel node technique. The book concludes with a chapter devoted to nuclear medicine therapy. This practical and up-to-date guide to nuclear medicine is ideal for beginners and will also help professionals who need to retrieve useful information rapidly.